Sound Horeg and Ritual Summons: A Philosophical Study of Tolerance in Indonesia through the Abu Dhabi Document - Kareli, Vincentius Yossy; Marianta, Yohanes I Wayan; Lego, Efrem Dwi Valencio Dowa; Purnanto, Antonius Hari (Abrahamic Religions: Jurnal Studi Agama-Agama, 2026)
The public debate over the fatwa declaring Sound Horeg haram has sparked new reflections on shared spaces in Indonesia's diverse society. Sujiwo Tejo refers to this phenomenon as audio pollution, comparable to the ritual religious calls that often ring out at certain times of day, highlighting the need for careful discussion in reconsidering the use of loudspeakers in public spaces for the sake of communal harmony and justice. This phenomenon shows that religious practices can cause social friction when public spaces are not managed fairly for all citizens. This paper analyzes the dynamics of religious tolerance in Indonesia through a literature review and analysis of relevant literature, using the 2019 Abu Dhabi Document as an ethical foundation that emphasizes human brotherhood and rejects the manipulation of religion. The findings show that the roots of intolerance often stem from a narrow understanding of faith and the interests of religious elites that have the potential to divide unity. Nevertheless, sincere and constructive dialogue is the way to foster mutual respect and strengthen peaceful coexistence amid diversity